2021
DOI: 10.1101/2021.04.16.440123
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The UBAP2L ortholog PQN-59 contributes to stress granule assembly and development inC. elegans

Abstract: When exposed to stressful conditions, eukaryotic cells respond by inducing the formation of cytoplasmic ribonucleoprotein complexes called stress granules. Stress granules are thought to have a protective function but their exact role is still unclear. Here we use C. elegans to study two proteins that have been shown to be important for stress granule assembly in human cells: PQN-59, the ortholog of human UBAP2L, and GTBP-1, the ortholog of the human G3BP1 and G3BP2 proteins. Both proteins fall into stress g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In agreement with these findings, we found that a 20 min shift from 20°C to 30°C was sufficient to increase the intensity of Nup foci in growing oocytes by Appendix Fig S4A and D) and significantly increase Nup condensation in embryos (Fig 4B). In contrast, the same conditions of oocyte arrest and mild heat stress did not change the distribution of the stress granule protein G3BP, which requires exposure to higher temperatures to condense (Abbatemarco et al, 2021;Fig 4A). Together these observations indicate that Nup foci assembly is readily enhanced by mild stress conditions.…”
Section: Nup Foci Assembly Is Enhanced By Oocyte Arrest Heat Stress A...mentioning
confidence: 93%
“…In agreement with these findings, we found that a 20 min shift from 20°C to 30°C was sufficient to increase the intensity of Nup foci in growing oocytes by Appendix Fig S4A and D) and significantly increase Nup condensation in embryos (Fig 4B). In contrast, the same conditions of oocyte arrest and mild heat stress did not change the distribution of the stress granule protein G3BP, which requires exposure to higher temperatures to condense (Abbatemarco et al, 2021;Fig 4A). Together these observations indicate that Nup foci assembly is readily enhanced by mild stress conditions.…”
Section: Nup Foci Assembly Is Enhanced By Oocyte Arrest Heat Stress A...mentioning
confidence: 93%